Managerial Approaches of Selected Government Executives to Basic Communication on the Job - Ribaya, E T (KnE Social Sciences, 2018)
The study aims to determine the approaches of selected government executives to basic communication on the job, specifically their level of confidence and assertiveness in communication skills which are essentials for good leadership. The paper also seeks to correlate the executives’ communication skills to intellective and nonintellective variables. A descriptive method of research was employed and no sampling scheme was utilized because the whole population consisting of ninety-seven middle managers was used as respondents and purposively selected from Department of Finance (DOF), Department of Transportation and Communication (DOTC), Department of Labor and Employment (DOLE) and Department of Interior and Local Government (DILG). Findings revealed that most of the respondents are aged 36-45 years old, female, bachelor’s degree holders, married and rendered 11-15 years of service in their respective government agencies. Results manifested that the respondents are highly effective in their technical skills, moderately effective in their interpersonal skills, and highly effective in their conceptual skills. When grouped by variables, the respondents are overall moderately effective in their managerial skills, and the overall level of confidence and assertiveness of the respondents in their approaches to basic communication on the job in all managerial skills is less confident and assertive regardless of variables. Data disclosed that there is no significant correlation between the respondents’ managerial skills and level of confidence and assertiveness when grouped according to variables. Therefore, there is also no significant correlation of the respondents’ overall level of confidence and assertiveness when grouped according to variables. Keywords: Government Executives, Managerial Skills, Confidence, Assertiveness, and Communication